“Universal Threads: Exploring Inherent Patterns Across Languages” (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Language universals, inherent patterns and structures found across diverse languages, serve as a fascinating area of study in linguistics. This article delves into the core concept of language universals, exploring their historical evolution and the characteristic features that transcend linguistic diversity. From syntactic structures to semantic concepts and phonological elements, the examination extends to controversies within the linguistic community and practical implications. By deciphering language universals, this article sheds light on the fundamental building blocks of human communication, with potential applications ranging from education to artificial intelligence.